The Effects of Self- Regulation Program on Sugar Consumption Behavior and Glycemic Level for Pregnant Women with Gestational Diabetes Mellitus Women in Community in Samut Sakhon Province - Dulyamakamyon, Ruttiya; Nimit-arnun, Nongpimol; Roojanavech, Sasitorn (Journal of The Royal Thai Army Nurses, 2020)
This quasi-experimental study, two group pretest-posttest design, aimed at study the effects of self-regulation program on sugar consumption behavior and glycemic control level among gestational diabetes mellitus women. The samples were purposive sampling and divided into experimental group (n = 33) and comparison group (n = 32). The experimental group received 8-weeks self-regulation intervention program those consisted 3 stages: 1) self-monitoring 2) self-evaluation and 3) self-reaction. The research instrument composed of 3 set of questionnaires; data based, attitude of sugar- beverage consumption, and food-beverage sugar consumption behaviors. Those were analyzed using descriptive statistics and t-test for mean score comparison. The results of study revealed that after joining the program, experimental group had higher mean score of sugar consumption attitude and behaviors, and lower mean score of blood sugar level statistically significant (p-value<.05). While posttest comparison between group, the experimental group showed lower mean score of blood sugar level than the comparison group statistically significant (p-value<.05). The researcher recommends that this intervention program should be utilized for self-regulation skill enhancement related to sugar consumption behaviors, in order to reducing harmfulness in both mothers and their child.